Protein backbone flexibility pattern is evolutionarily conserved in the flaviviridae family: a case of NS3 protease in flavivirus and hepacivirus - Palanisamy, Navaneethan; Akaberi, Dario; Lennerstrand, Johan (Molecular phylogenetics and evolution, 2018)
Viruses belonging to the Flaviviridae family have been an important health concern for humans, animals and birds alike. No specific treatment is available yet for many of the viral infections caused by the members of this family. Lack of specific drugs against these viruses is mainly due to lack of protein structure information. It has been known that protein backbone fluctuation pattern is highly conserved in protein pairs with similar folds, in spite of the lack of sequence similarity. We hypothesized that this concept should also hold true for proteins (especially enzymes) of viruses included in different genera of the Flaviviridae family, as we know that the sequence similarity between them is low. Using available NS3 protease crystal structures of the Flaviviridae family, our preliminary results have shown that the Cα (i.e. backbone) fluctuation patterns are highly similar between Flaviviruses and a Hepacivirus (i.e. hepatitis C virus, HCV). This has to be validated further experimentally.